Pathological and microbiological investigations into cases of bacterial chondronecrosis and osteomyelitis in broiler poultry. Issue 6 (2nd November 2017) - Wijesurendra, Dinidu S.; Chamings, Anthony Neal; Bushell, Rhys Nathan; Rourke, Denise O'; Stevenson, Mark; Marenda, Marc Serge; Noormohammadi, Amir H.; Stent, Andrew
ABSTRACT: Bacterial chondronecrosis and osteomyelitis (BCO) is increasingly recognized as a major cause of lameness in commercial broilers chickens worldwide, but the pathogenesis of the condition is incompletely understood. This was a longitudinal study of 20 commercial broiler farms in Victoria, Australia, to investigate the aetiology and pathology of BCO. Thorough postmortem examination was performed on culled and dead birds ( n  = 325) from 20 different flocks at either 1 week, 4 weeks or 5 weeks of age and samples were analysed by conventional bacteriology, molecular identification of infectious organisms detected, serology and histopathology. BCO occurs throughout the life of broiler flocks at a very high rate, with lesions detected in 28% (95% CI 23–34%) of the mortalities and culls. The condition occurs with similar prevalence in both the femur and tibiotarsus. BCO is an infectious process that appears to result from bacteraemia and haematological spread of bacterial pathogens, especially Escherichia coli, to the bones, with 65.3% bacterial isolates from histologically confirmed BCO identified as E. coli, 11.5% as Staphylococcus and the remainder composed of mixed infections or a range of other minor isolates. We observed that almost all E. coli isolated from cases of BCO are avian pathogenic E. coli, suggesting that preventative measures should be directed at this organism.